2011
DOI: 10.1148/radiol.11102128
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Twinkling Artifact for Renal Calculus Detection: Correlation with CT

Abstract: Purpose:To retrospectively correlate sonographic color Doppler twinkling artifact within the kidneys with unenhanced computed tomography (CT ) in the detection of nephrolithiasis. Materials and Methods:Institutional review board approval was obtained for this retrospective HIPAA-complaint investigation, and the informed consent requirement was waived. Sonographic imaging reports describing the presence of renal twinkling artifact between January 2008 and September 2009 were identifi ed. Subjects who did not un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 16 publications
3
61
0
3
Order By: Relevance
“…Stones typically appear as echogenic foci within the collecting system that cast acoustic shadows, but either finding may be absent. A twinkling artifact (nonvascular color signal) on Doppler imaging has been proposed as an additional method to detect stones, but it has poor sensitivity and specificity (16).…”
Section: Massesmentioning
confidence: 99%
“…Stones typically appear as echogenic foci within the collecting system that cast acoustic shadows, but either finding may be absent. A twinkling artifact (nonvascular color signal) on Doppler imaging has been proposed as an additional method to detect stones, but it has poor sensitivity and specificity (16).…”
Section: Massesmentioning
confidence: 99%
“…In a study by Dillman et al (9), the false positivity of twinkling artifact compared with CT was 51% (75 of 148 twinkling foci). Winkel et al (11) also compared CT findings with sonographic and Doppler findings and reported that the addition of color Doppler to grayscale US decreased the PPV for the diagnosis of calculi from 81% to 67% due to increased false positive foci on Doppler US.…”
Section: Discussionmentioning
confidence: 94%
“…However, lower detection rates have also been reported in the literature. Dillman et al (9) reported the sensitivity of twinkling artifact to be 55% (9). Our results for color Doppler US were closer to their study, with 41.3% (95% CI, 30.3-52.8) sensitivity for detection of calculi smaller than 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Liegt eine Ektasie vor, so verbessert sich die Sensitivität für eine Urolithiasis von 57 auf 81% [19]. Zwar kann ein postobstruktives Farbartefakt (Twinkling-Effekt) die Lokalisationsdiagnostik verbessern, die Sensitivität hierfür ist mit 55% aber eher schwach [7,37]. Zusätzlich weist eine Erhöhung des Resistance-Index (RI) der Aa.…”
Section: Sonographieunclassified